Determination of regional relationships among Salmonella spp. isolated from retail pork circulating in the Chiang Mai municipality area using a WGS data approach - Prapas Patchanee (2018)
© 2017 Elsevier B.V. Salmonella is recognized as a significant zoonotic foodborne pathogen, and pork products are involved in one-fifth of infections. Whole genome sequencing data of Salmonella isolated from retail's pork circulating in the Chiang Mai Municipality area between April 2013 and September 2014, were used to focus on genetic diversity and proven in pig-human transmission based on Multilocus Sequence Typing (MLST). Additionally, WGS data were used to investigate virulence genes, to assess the hazard or pathogenic potential transferred into the food production chain. In this study, all 32 Salmonella strains were classified into 11 Sequence Types (STs). ST469 accounted for the majority (41%). The sequence types of two other strains, 6% of the total, could not be identified. All tested strains carried at least 15 virulence genes. The most frequent gene profile was “sfm-fim-sop-inv.-org-sip-spa-sif-fli-flg-hil-spr-ssa-sse-pag-bss” (47%). Salmonella circulating in the study area demonstrated competence in biofilm production, host cell adhesion, host cell invasion, and host cell survival. Based on the phenotypic and genotypic findings, as well as pathogen source, it appears possible that a common supply chain or common infection source might be presented in the retail pork system in the study area. In addition, an epidemiological comparison of the Salmonella genotypes from the current study with those from other areas such as People's Republic of China (PR China) and the Lao People's Democratic Republic (Lao PDR) was generated by Minimum spanning tree (MST). Identical strains originating from humans, animals and food were found. The findings indicate that contamination can be occured at all levels including pre-harvest, the farm-slaughterhouse-retail chain and consumers over different geographical areas. Acquiring information about infection sources and transmission routes will hopefully motivate all sectors to enforce strict sanitation controls at all production stages including the consumer level.